A Socialised Medical Service (London : The Socialist Medical Association, 1933)
1933 1933 1930s 21 pages Unfortunately, at the periphery there is at the present time an even larger number of different authorities dealing with health matters. As an example of the present muddle there are Sanitation, Infectious Diseases, Maternity and Child Welfare, Tuberculosis, V.D., amongst other matters, dealt with by Public Health Committees, of which there are two to deal with even area except County Boroughs, i.e., a Public Health Committee of the County Council and also a Public Health Committee of the local Sanitary Authority; the inspection and treatment of school children by the Education Committees; and the Poor Law Medical Service, as well as a good many hospitals up and down the country still under the control of the Public Assistance Committees. The important branch of curative medicine, National Health Insurance and the Factory Health Service, as far as it exists at all, is administered directly by the Home Office. The problem of the future is the evolution and transformation of all those branches of medical activity and the carrying out of the necessary administrative changes, so that they may be controlled by a single health authority in each locality. It will be convenient to consider the changes necessary under four heads:— (1) National Health Insurance. (2) Poor Law. (3) Hospital Services. (4) Public Health Services. It must be remembered, however, that the development of all these four services should take place synchronously, and as rapidly as public opinion will permit. 1. — NATIONAL HEALTH INSURANCE National Health Insurance is composed of two distinct sections which have really no direct connection with one another; cash benefit and medical benefit, by which latter is described the limited treatment provided by the National Health Insurance Act. Now there is a good deal to be said for the retention of the administration of cash benefit by the Approved Societies, but the treatment of sickness in the insured being a matter of national as well as personal importance is much better in the hands of an authority that is dealing with other medical problems and has to consider questions of prevention as well as cure. Accordingly, one of the first steps must be the transference from the Insurance Committees to the local health authorities of the administration of medical benefit. To ensure that the valuable experience gained by the present members of the Insurance Committees may not be lost, it may be wise to allow co-option to the extent of one-third by the sub-committees of the Public Health Committees, which will necessarily be formed for the administration of medical benefit. 16 292/847/1/1